FREQUENCY OF DEVELOPMENTALLY MALFORMED PERMANENT MAXILLARY LATERAL INCISORS IN PATIENTS VISITING THE THREE TEACHING DENTAL HOSPITALS OF PESHAWAR - Ijaz, Faiza; Khattak, Munawar Aziz; Nofil Ahmad; Sana Arbab; Syed Amjad Shah; Iram Abbas (Journal of Ayub Medical College Abbottabad, 2021)
Background: The permanent maxillary lateral incisor (PMLI) shows morphological variations, in the form of different crown shapes such as peg-shaped, cone-shaped, barrel-shaped and canine-shaped. The frequency of developmentally malformed permanent maxillary lateral incisors varies among different populations. The aim of this study was to document the frequency of different shapes of developmentally malformed permanent maxillary lateral incisors in patients visiting the three teaching dental hospitals of Peshawar. Methods: It was a cross-sectional study conducted in the Oral Diagnosis department of Peshawar Dental College, Sardar Begum Dental College, and Khyber College of Dentistry from 1st Sep 2018 to 15th June 2019. A total of 82 subjects were included that fulfilled the inclusion criteria. Shape of the malformed PMLI was determined using Computer-aided design/Computer-aided manufacturing software. Descriptive statistics including frequencies and percentages for observed developmental malformation and their types were computed and Chi-square test was applied to see the relation between various shapes and their occurrence with respect to site and position within the jaws. Results: The peg shaped PMLI was seen in 81 (98.87%) patients and barrel shaped was present in 1 (1.22%) patient. The malformed PMLIs was found to be unilateral in 38 (46.3%) and bilateral in 44 (53.7%) patients, with more common presence on both sides 44 (53.7%) followed by right side 20 (24.4%) and left side 18 (22.0%). Conclusion: The subjects having predominant developmental malformation in case of permanent maxillary lateral incisor was peg-shaped permanent maxillary lateral incisor.